South Russian Diasporas: Institutional Profile, Problems of Loyalty and Legitimacy - Anton V. Serikov, Anatoly V. Lubsky, Andrey V. Bedrik, (Opción, 2019)
This article analyses the existing ethnic structure of the population of the Rostov Oblast and the Stavropol Krai. The methodology of this research is based on the socio-cultural and institutional approaches in sociology. Contradictions between the degree of loyalty and the level of legitimacy were revealed, since loyalty often stands rejected or condemned by diaspora members. This contradiction appears to reduce the consolidation potential for diasporas at the inter-ethnic and intra-ethnic levels. Grounds for overcoming this contradiction can be found in a direct dialogue between the state and the national communities based on common public values.